2017
DOI: 10.1159/000484207
|View full text |Cite
|
Sign up to set email alerts
|

Opioid Receptors Contribute to Antinociceptive Effect of Tianeptine on Colorectal Distension-Induced Visceral Pain in Rats

Abstract: Tianeptine is a clinically effective atypical antidepressant with distinct neurochemical properties. In this study, we aimed to investigate the contribution of opioid receptors in the antinociceptive effect of tianeptine on visceral pain in awake rats and to differentiate the subtype and the localization (central and/or peripheral) of these opioid receptors involved in this antinociception. Visceromotor response to noxious colorectal distension (CRD) was quantified with electromyographic recordings, obtained f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 41 publications
(69 reference statements)
0
5
0
Order By: Relevance
“…administration of CEMR-1 and CEMR-2 produced more potent analgesia than their respective parent peptide in acetic acid-induced visceral pain. A recent investigation reported that antinociceptive effect of the opioids on colorectal distension-induced visceral nociception involved the activation of both central and peripheral opioid receptors (Bilge et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…administration of CEMR-1 and CEMR-2 produced more potent analgesia than their respective parent peptide in acetic acid-induced visceral pain. A recent investigation reported that antinociceptive effect of the opioids on colorectal distension-induced visceral nociception involved the activation of both central and peripheral opioid receptors (Bilge et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, an opioid-related mechanism was proposed to explain the antinociceptive effects of tianeptine. Antagonists of all opioid receptor types (μ, δ, and κ) prevented the antinociceptive effect of tianeptine in rats with visceral nociception [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies demonstrated synergistic or additive interaction between some drugs [ 25 , 26 ]. It has been reported that the antinociceptive effects of gabapentin and tianeptine were reversed by an opioid receptor antagonist at the spinal level [ 24 , 27 ]. On the other hand, serotonergic and noradrenergic systems are involved in the antinociception of tianeptine, but not that of gabapentin [ 24 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the paper [169], with the help of a radioactively labelled ligand, it was shown in cell cultures from humans and mice that tianeptine is a high-affinity μ-opioid receptor agonist, a medium-affinity full δ-opioid receptor agonist, and is not a κ-opioid receptor agonist. The authors of [170] caused visceral pain in rats by colorectal distension. The antinociceptive effect of tianeptine disappeared after injection of naloxone (opioid receptor antagonist).…”
Section: Psychotropic Drugs For Management Of Pain and Itching Synmentioning
confidence: 99%